2019
DOI: 10.2166/wst.2019.037
|View full text |Cite
|
Sign up to set email alerts
|

Use of broken brick to enhance the removal of nutrients in subsurface flow constructed wetlands receiving hospital wastewater

Abstract: Eight horizontal subsurface flow pilot scale artificial wetlands were constructed to evaluate the effectiveness of broken brick to remove nutrients from hospital wastewater. The average total suspended solids (TSS), 5-day biochemical oxygen demand (BOD5), chemical oxygen demand (COD), total Kjeldahl nitrogen (TKN), NH4-N, NO3-N, and phosphate percent removal efficiency of constructed wetlands were, respectively, 93.2%, 90.4%, 83.7%, 64%, 64.3%, 52.1% and 56.1% in the dry season and 89.7%, 85.8%, 82.9%, 66%, 62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Absolute abundances of ARB were reduced from the influent to the effluent by up to 93.2%. Dires et al (2018Dires et al ( , 2019) also highlighted the role of vegetation in CWs, as they observed that ARB removals were higher in planted CWs (81% -93%) than in unplanted wetlands (42% -74%). Plants do not seem to be directly involved in the removal efficiency of ARGs, but they are involved indirectly.…”
Section: Removal Of Antibiotics Other Ppcps Arb and Args In Construct...mentioning
confidence: 97%
See 1 more Smart Citation
“…Absolute abundances of ARB were reduced from the influent to the effluent by up to 93.2%. Dires et al (2018Dires et al ( , 2019) also highlighted the role of vegetation in CWs, as they observed that ARB removals were higher in planted CWs (81% -93%) than in unplanted wetlands (42% -74%). Plants do not seem to be directly involved in the removal efficiency of ARGs, but they are involved indirectly.…”
Section: Removal Of Antibiotics Other Ppcps Arb and Args In Construct...mentioning
confidence: 97%
“…Higher relative surface area, micropores and Si-OH structures for chemical sorption and microbial attachment improve the removal of ARGs (Hu et al, 2012). Dires et al (2018Dires et al ( , 2019) evaluated the effectiveness of broken brick as filtering material in 8 HSSF-CWs (mesocosms scale) to remove nutrients and ARB from hospital wastewater in Ethiopia.…”
Section: Removal Of Antibiotics Other Ppcps Arb and Args In Construct...mentioning
confidence: 99%
“…Dires et al [67] compared the nitrogen and P removal capabilities of planted (sugar cane) and non-planted CWs and discovered that planted wetlands had a greater capacity to eliminate nitrogen and P, which was probably due to the stimulation of the plant rhizosphere to produce more microbes. Through phytoremediation [68], plants remove contaminants such as antibiotics, heavy metals, and pathogens.…”
Section: Plantsmentioning
confidence: 99%
“… M1, M2, M3A, M3B = 800 L/h, M4, M5 = 300 L/h M1, M2, M3A, M3B = 1.13 h, M4, M5 = 1.67 h Pilot-scale [113] Study 9 Denmark MBR followed by 450 mg/L of PAC 2.2 m 3 /day 35 days Pilot-scale [10] Study 10 Denmark MBR 2.2.m 3 /day 35 days Pilot-scale [10] Study 11 Ethiopia Waste Stabilization Ponds: 2 facultative ponds (667 m 2 ), 2 maturation ponds (401 m 2 , 396 m 2 ), and 1 fish pond (862 m 2 ) 29 days Full-scale [117] Study 12 Ethiopia 8 horizontal subsurface flow CWs (4 m length, 1.2 m width and 0.6 m depth) with gravel and broken brick media as substrate. 165.75 L/day 4 days Pilot-scale [12] , [97] Study 13 Finland Ultrafiltration followed by pulsed corona discharge (30 W was applied for 1 kWh /m 3 of pulse energy delivered) Pilot-scale [119] Study 14 Spain MBR (11 m 3 ) with 10 flat sheet (FS) chloral polyethylene membranes (0.8 m 2 each). Coarse bubble aeration was provided, MLSS- 8 g/L 100 L/h 50 h 30 days [100] Study 15 ...…”
Section: Pilot/full-scale Treatment Systems For Hww Managementmentioning
confidence: 99%